Penerapan Data Mining Klasifikasi Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Sistem Informasi di Program Studi Sistem Informasi - Dimas Ainnur Ryanda Saragih; M Safii; Dedi Suhendro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The purpose of this study was to determine the effect of Academic Information System services on student satisfaction so that students who are academics do not feel disappointed with services related to Academic Information Systems. Measurement of Student satisfaction related to campus Information System services is rarely done so that the level of student satisfaction is unknown. By knowing the level of student satisfaction, the College can improve the service if it is not good and further improve the service if the level of satisfaction is good. This study measures the level of student satisfaction with the services of the Academic section at STIKOM Tunas Bangsa. The method used in this study is C4.5 Algorithm, where the data source used uses a questionnaire / questionnaire technique that is given to students randomly in the STIKOM Tunas Bangsa Pematangsiantar environment. Data validity is done with internal validity. The variables used include (1) System Quality, (2) Information Quality, (3) Service Quality, and (4) Performance Expectations. It is expected that the results of this research can be applied to improve the Academic Information System service so that the existing system can run better